Reflections on Nicaraguan trade unionism (1970-2015) - Guerra Vanegas, Jorge (Universidad Nacional Autónoma de Nicaragua, Managua. UNAN-Managua, 2016)
The Nicaraguan labor movement during the period 1970, to the present despite political situation has played an important role in the history of national. This paper aims to recount this movement in recent times. During the research period the labor movement taking advantage of structural opportunities has led strikes, armed actions, alliances, negotiations in order to make their presence felt on the national political scene. One of the characteristics of this social movement is that their collective action consolidates in periods of social, political and economic crisis. To achieve social and political rights: freedom of association, social security, working hours, among others, is one of the great contributions of of syndicalism to the Nicaraguan contemporary history. With the electoral defeat of the FSLN in 1990, the opportunity structures changed, and thus the repertoires of confrontation. In this new scenario alliances, negotiations and strikes occurred as well as a weakening of the trade union movement due to the structural adjustment policies of that period. Thus, innovative expressions of unionism are given: Confederation of self-employed, and the Women s Movement of the maquilas, important in the recent history of syndicalism, thereby presenting new forms of collective action in a new context of national reality.Key words: Labor movement, Popular Sandinista Revolution, Women s Movement of the maquilas, Confederation of self-employed.